Relationship of Stage of Labour at Time of C-Section and Subsequent Preterm Delivery in Females Presenting with Singleton Pregnancy - Raffique, Sidra; Rasool, Saba; Maqbool, Amna; Bashir, Maria; Mansoor, Maheen; Rauf, Abdul (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Preterm birth remains a large public health concern and contributor to neonatal morbidity. The effect of a cesarean in different stages of labor on spontaneous preterm birth (sPTB) in a subsequent pregnancy has not been extensively studied. Aim: To assess the association of subsequent preterm delivery with second stage of labour at time of cesarean delivery in previous pregnancy in females presenting with singleton pregnancy. Study design: Cohort study Place and duration of study: Unit IV, Department of Obstetrics & Gynecology, Sir Ganga Ram Hospital, Lahore from August 2017 to February 2018. Methodology: A total of 180 patients who was fulfill the selection criteria included in the study. Females were asked for stage of labour at time of cesarean section in previous pregnancy and two groups were formed. Group I females with C-section at first stage and group II females with C-section at second stage. Then all patients were followed-up in OPD till delivery of index pregnancy. Statistical analysis was done using SPSS version 20. Results: The mean age in all cases was 30.95±5.55 years with minimum and maximum age as 20 and 40 years. The mean age in group-I was 31.09±5.71 years and the mean age in group-II was 30.81±5.40 years. The mean parity in group-I and group-II was 2.78±0.92 and 2.82±0.84. The mean gestational age in group-I and group-II was 39.04±1.94 weeks and 38.22±3.05 weeks respectively. In group-I 4(4.4%) cases and in group-II 15(16.7%) cases had preterm birth, the preterm birth was higher in group-II as compared to unexposed group-I, pvalue <0.05. The RR = 0.267 shows protective effect on PTB in group-I. Conclusion: Through the findings of this study we found significant association of subsequent preterm delivery with second stage of labour at time of cesarean delivery in previous pregnancy in females presenting with singleton pregnancy. So females with previous LSCS must be screened timely to prevent subsequent preterm birth. By minimizing subsequent preterm birth we can reduce related neonatal mortality.